2003
DOI: 10.1080/0963818031000087862
|View full text |Cite
|
Sign up to set email alerts
|

Management Accounting and Information Systems: Erp Versus Bob

Abstract: The purpose of this study is to compare the use of enterprise resource planning (ERP) and best of breed (BoB) standalone systems in practice. The data for the study were collected through a postal questionnaire in 300 large and middle-sized industrial units in Finland. The questionnaire addressed questions concerning IS implementation (why, how and by whom the IS project was introduced), management accounting function, and the use of advanced management accounting techniques. The results obtained indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
4
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 12 publications
3
73
4
5
Order By: Relevance
“…Nevertheless, research that has focused on the initiator's role in the initiation of accounting information systems is still scarce. Hyvönen (2003) shows that there is a link between the accounting profession and IT system design. His results further indicate that the initiator of a new IT system has an impact on what kind of system will ultimately be implemented.…”
Section: The Role Of Initiator In the Initiation Of New Systems/technmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, research that has focused on the initiator's role in the initiation of accounting information systems is still scarce. Hyvönen (2003) shows that there is a link between the accounting profession and IT system design. His results further indicate that the initiator of a new IT system has an impact on what kind of system will ultimately be implemented.…”
Section: The Role Of Initiator In the Initiation Of New Systems/technmentioning
confidence: 99%
“…Accordingly, our knowledge about this important relationship is still in its infancy. The notable exception is Hyvönen (2003), who suggests that accounting departments have been advocating more stand-alone systems than fully integrated systems. However, in contrast to these findings, HenttuAho (2016) found that accountants can have a positive influence on the integration of numbers within financial forecasting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A BoB strategy involves interfacing the 'best' available softwares for each function and therefore they do not automatically share a common database (Miranda, 1999;Moriarty, 1999;Hyvonen, 2003). The functionality required from the system, the ability of your own IT department, the resulting relationship with the vendors and of course the cost, are the major issues you have to examine when deciding between an ERP system and a BoB system.…”
Section: Literature Reviewmentioning
confidence: 99%